Transcutaneous auricular vagus nerve stimulation in healthy individuals, stroke, and Parkinson’s disease: a narrative review of safety, parameters, and efficacy - Matsuoka, Machiko; Yamaguchi, Tomofumi; Fujiwara, Toshiyuki (Frontiers in Physiology, 2025)
Among the noninvasive electrical stimulation methods, transcutaneous auricular vagus nerve stimulation (taVNS) regulates the activity of various neural networks in the brain and autonomic nervous system and is expected to be applied clinically in many areas, including in patients with central nervous system, psychiatric, and cardiac diseases. Although systematic reviews and meta-analyses have been conducted on safety and efficacy, the variability of stimulation parameters and the lack of consistency in their effects remain significant issues. Therefore, the present study aimed to provide a comprehensive view of the safety, parameters, and efficacy of taVNS by focusing on studies in healthy participants, patients with stroke, and patients with Parkinson’s disease. A literature search was conducted from October 14 to 25 November 2024, using PubMed, Google Scholar, Web of Science, the Cochrane Library, and Scopus. The following search terms were used: “noninvasive VNS or nVNS or noninvasive vagus nerve stimulation,” “transcutaneous vagus nerve stimulation or tVNS,” and “transcutaneous auricular vagus nerve stimulation or taVNS.” In total, 154 papers were included, of which 139 were on healthy participants, nine on patients with stroke, and six on patients with Parkinson’s disease. The safety of taVNS was relatively high. Although minor side effects were reported, no serious adverse events were attributed to taVNS parameters used. taVNS could regulate brain activity, motor and mental functions, and autonomic nervous system activity in patients with stroke and Parkinson’s disease. Modulation of the autonomic nervous system and cortical excitability was also observed in healthy individuals. However, these effects may depend on the stimulation parameters. The lack of reports on safety and the stimulation parameters used was also highlighted. Further validation of parameters and accumulation of evidence regarding the efficacy of taVNS are necessary.